Age, Growth and Spatial Distribution of the Life Stages of the Shortfin Mako, Isurus oxyrinchus (Rafinesque, 1810) Caught in the Western and Central Atlantic. - Rodrigo R Barreto; Wialla K T de Farias; Humber Andrade; Francisco M Santana; Rosangela Lessa (PLoS ONE, 2016)
The shortfin mako (Isurus oxyrinchus) is a highly migratory pelagic shark that preferentially inhabits oceanic regions in practically all oceans. The wide distribution range of this species renders it susceptible to coastal and oceanic fishing operations. The International Union for Conservation of Nature (IUCN) and the International Commission for the Conservation of Atlantic Tunas (ICCAT) consider this species to be highly vulnerable, especially due to its biological parameters, which are different from those of other sharks that occupy the same niche (e.g., Prionace glauca). Consequently, considerable declines in abundance have been detected over various parts of its range, most of which are linked to oceanic longline fishing. The species has conflicting life history parameters in studies conducted in the last 30 years, especially with regard to age and growth. The main discrepancies regard the interpretation of the periodicity of the deposition of band pairs (BPs) on vertebrae and the possibility of ontogenetic variations in growth. Shortfin mako sharks (n = 1325) were sampled by onboard observers of the Brazilian chartered pelagic longline fleet based in northeast Brazil from 2005 to 2011. Lengths were 79 to 250 and 73 to 296 cm (fork length, FL) for males and females, respectively, with a statistically significant difference in size between sexes and differences in the proportion of individuals in each size class. The onboard observers collected a subsample of vertebrae (n = 467), only 234 of which were suitable for analyses. Reliability between readings was satisfactory. However, it was not possible to validate periodicity in the formation of age bands in the sample. Thus, the von Bertalanffy growth function was used to calculate growth rates for the species through the interpretation of BPs in different scenarios: one BP per year (s1), two BPs per year (s2) and two BPs per year until five years of life (s3). Growth parameters varied for both females (Linf = 309.7[s3] to 441.6[s1]; k = 0.04[s1] to 0.13[s3]; t0 = -7.08[s1] and -3.27[s3]) and males (Linf = 291.5[s3] to 340.2[s1]; k = 0.04[s1] to 0.13[s3]; t0 = -7.08[s1] and -3.27[s3]). To advance the understanding of the use of habitat, the first analysis of the spatial distribution of the life stages of the shortfin mako sharks caught by commercial longline fishing operations in the South Atlantic was performed. The findings indicate that the portion of the population exploited by the fleets is predominantly juvenile and future actions should take the following issues into account: improvements in the efficiency of data collection procedures, the reestablishment of the onboard observer program, emergency investments in studies that can contribute to a better understanding of habitat use and life history theory.